Simultaneous extraction of copper and iron from chalcopyrite concentrate via surfactant-assisted chlorination leaching - Choudhari R.; Singh J.K.; Mishra D.; Sinha S.; Shekhar S.; Sahu K.K. (My University, 2025)
Among several non-ferrous metals, copper is a vital metal having wide industrial applications and is mainly found to be associated with sulfides. Numerous pyro- and hydro-metallurgical processes were developed to extract copper from such sulfide minerals. However, due to dwindling grades of copper ore, hydrometallurgical methods are being increasingly used and gaining popularity. High temperature-based oxidation-leaching techniques are usually adopted, while higher recovery of copper at ambient temperature is still challenging. In this regard, an attempt has been made to develop a low-temperature chlorine gas leaching process to maximize copper dissolution from sulfides ores. In this work, chalcopyrite leaching was carried out in the presence of gaseous chlorine in an aqueous solution within the temperature range of 278 K to 293 K and atmospheric pressure. Low-temperature leaching with chlorine gas is found to be more efficient as compared to oxidative leaching processes. However, the challenge is to overcome the slow leaching kinetic caused by passivation. An attempt has been made to address this problem by using a strong oxidizing agent (Cl2 gas) in this study. Surfactant-mediated-chlorine leaching further improves the recovery as it helps to overcome the passivation issue by dispersing the elemental Sulphur. Tri-chloro-ethylene (C2HCl3) (TCE) has been used as an ‘S’ dispersant. Various process parameters, such as solid-to-liquid ratio, gas flow rate, and leaching temperature, were studied and optimized. The recovery of copper was found to be only 70% at 285 K without any surfactant addition, whereas it will increase to 94.8% after the addition of only 2% (v/v) tri-chloro-ethylene (TCE). Copyright © 2023 Elsevier Ltd. All rights reserved.